2009
DOI: 10.4161/isl.1.1.8629
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of osteopontin in type 1 diabetes

Abstract: (NOD) mice. 17 However, data concerning the temporal changes in OPN expression in correlation with destructive insulitis and hyperglycemia in type 1 diabetes, and the intrinsic mechanisms that contribute to its regulation have not been reported.Previously, we demonstrated that high levels of pancreatic OPN correlate with the acute response to streptozotocin (STZ) induced diabetes in rodents. 18 Using an OPN knockout model, we showed that OPN is essential for polarizing the islet cytokine immune response toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…Osteopontin serves diverse roles including binding to calcium-based biominerals, such as calcium-phosphate, that is important to inhibition and regulation of bone mineralization [46]. Several physiological roles have also been identified for iOPN including cytoskeleton rearrangement, modulation of immune responses, and as an adaptor or scaffolding protein [42, 45, 47]. Similar to previous reports, we found that iOPN is highly expressed in human pancreatic islets and beta-cells [48].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Osteopontin serves diverse roles including binding to calcium-based biominerals, such as calcium-phosphate, that is important to inhibition and regulation of bone mineralization [46]. Several physiological roles have also been identified for iOPN including cytoskeleton rearrangement, modulation of immune responses, and as an adaptor or scaffolding protein [42, 45, 47]. Similar to previous reports, we found that iOPN is highly expressed in human pancreatic islets and beta-cells [48].…”
Section: Discussionsupporting
confidence: 86%
“…A wide range of inflammatory cytokines and growth factors have been shown to regulate expression of iOPN including LPS, NO, IL-1β, IFN-γ, and TNF-α [42, 43, 45, 47]. Hyperglycemic conditions and the incretin hormone glucose-dependent insulinotropic polypeptide (GIP) also increase OPN mRNA and protein content in pancreatic islets [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning roles of diabetes mellitus on BBB permeability and changes in gene expression, the previous papers showed increased BBB permeability in diabetes mellitus. [41][42][43] In addition, other papers indicate that CD36 expression is increased in murine models of diabetes mellitus, 79 that high levels of osteopontin expression is seen in diabetic animals, 80,81 and that high plasma glucose increases the expression of MMP-13 in vessels. 82 Thus, it is likely that hyperglycemia as well as hypertension and cerebral ischemia induces BBB damage followed by the increased expression of these molecules (Fig.…”
Section: Overall Summary and Discussionmentioning
confidence: 99%
“…It is believed that extracellular and intracellular OPN serves different biological roles [3]. In rodents, all major islet cells including the beta cells express OPN [4, 5]. The role of OPN in islets is not fully established but OPN seems to prevent apoptosis and stimulate proliferation of islets and insulin producing cells, suggesting an overall islet protective role [4, 6, 7].…”
Section: Introductionmentioning
confidence: 99%